Analisis Pengaruh Signifikan Antara Kualitas Produk dan Kepuasan Konsumen Menggunakan Metode Regresi Linear pada UMKM Qonita Rajut (UNISTEK, 2023)
Abstract UMKM Qonita knitting is a business engaged in manufacturing, one of which is a business that produces various kinds of products such as dresses, hats, sandals, shoes, blankets, and also knitted bags. The problem currently faced by the Qonita Knitting SMEs is to keep their business growing and stable, therefore the Qonita Knit SMEs want to conduct research on what factors have a significant influence between product quality and consumer satisfaction using a simple linear regression test method. In this study the data used is data obtained from consumers of UMKM Qonita Knitting customers. The data was obtained from filling out the questionnaire. The purpose of this research was to find out the significant factors between product quality and consumer satisfaction at the Qonita Knitting UMKM. The results of this study indicate that the correlation is 0.930. So it can be concluded that there is a significant influence on product quality and consumer satisfaction. Therefore, the Qonita Knitting MSMEs must be able to maintain the quality of their products so that their business can develop and be stable. Keywords: Product Quality, Customer Satisfaction, Simple Linear Regression Test